Anti-N-Methyl-D-Aspartate Receptor Encephalitis with Catatonia Treated by Plasmapheresis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The case of a 12-year-old girl with anti-methyl-D-aspartate receptor (NMDAR) encephalitis is reported by researchers from Augsburg and Bonn, Germany, and Oxford, UK.